A novel gene mutation, c.82delC (p.Arg28 Alafs5), in a Korean family with X-linked agammaglobulinemia - Jeongeun Lee; Minhee Rhee; Taek Ki Min; Hae In Bang; Mi-Ae Jang; Eun-Suk Kang; Hee-Jin Kim; Hyeon-Jong Yang; Bok Yang Pyun (Korean Pediatric Society, 2016)
X-linked agammaglobulinemia (XLA) is a hereditary humoral immunodeficiency that results from Bruton's tyrosine kinase (BTK) gene mutations. These mutations cause defects in B-cell development, resulting in the virtual absence of these lymphocytes from the peripheral circulation. Consequently, this absence leads to a profound deficiency of lg all isotypes, and an increased susceptibility to encapsulated bacterial infections. A 15-month-old Korean boy presented with recurrent sinusitis and otitis media after 6 months of age, and had a family history of 2 maternal uncles with XLA. Laboratory tests revealed a profound deficiency of Ig isotypes, and a decreased count of CD19+ B cells in the peripheral circulation. Based on his family history and our laboratory test results, he was diagnosed with XLA. We performed BTK gene analysis of peripheral blood samples obtained from family members to confirm the diagnosis. Mutational analysis revealed a novel hemizygous frameshift mutation (c.82delC, p.Arg28Alafs*5), in the BTK gene. His mother and maternal grandmother were heterozygous carriers of this mutation and his two maternal uncles were hemizygous at the same position. After XLA diagnosis, intravenous immunoglobulin (400 mg/kg, monthly) treatment was initiated; recurrent sinusitis and otitis media were subsequently brought under control. To our knowledge, this is the first reported case of a Korean pedigree with a novel mutation in the BTK gene.